2016
DOI: 10.1111/nph.14179
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variability in phosphorus‐induced lipid remodelling among marine eukaryotic phytoplankton

Abstract: The response of marine microalgal lipids to phosphorus is of central importance in phytoplankton ecology but remains poorly understood. We determined how taxonomically diverse microalgal species remodelled their lipid class profile in response to phosphorus availability and whether these changes coincided with those already known to occur in land plants and in the limited number of phytoplankton species for which data are available. The complete lipid class profile and specific lipid ratios influenced by phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
48
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 70 publications
8
48
1
Order By: Relevance
“…This phenomenon of BL replacing PC under low P was shown to be common in freshwater and marine algae (Khozin-Goldberg and Cohen, 2006;Van Mooy et al, 2009;Martin et al, 2011;Iwai et al, 2015;Cañavate et al, 2017b). Recent studies comparing lipid class and P-uptake profiles of eight algae at low P i showed replacement of phospholipid by BL with concomitant high P uptake in the green alga Tetraselmis suesica and the stramenopiles P. tricornutum, N. gaditana, and P. atomus (Cañavate et al, 2017a(Cañavate et al, , 2017b. Phospholipid replacement and high P uptake under P stress indicate that these algae have a mechanism vital in temporal P limitation.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…This phenomenon of BL replacing PC under low P was shown to be common in freshwater and marine algae (Khozin-Goldberg and Cohen, 2006;Van Mooy et al, 2009;Martin et al, 2011;Iwai et al, 2015;Cañavate et al, 2017b). Recent studies comparing lipid class and P-uptake profiles of eight algae at low P i showed replacement of phospholipid by BL with concomitant high P uptake in the green alga Tetraselmis suesica and the stramenopiles P. tricornutum, N. gaditana, and P. atomus (Cañavate et al, 2017a(Cañavate et al, , 2017b. Phospholipid replacement and high P uptake under P stress indicate that these algae have a mechanism vital in temporal P limitation.…”
mentioning
confidence: 92%
“…Low P content triggering TAG increase also is seen in the model algae C. reinhardtii and P. tricornutum, additionally replacing extraplastidial phosphatidylcholine (PC) by taxonomically specific betaine lipid (BL) classes such as diacylglyceroltrimethylhomoserine (DGTS; Iwai et al, 2014;Abida et al, 2015). This phenomenon of BL replacing PC under low P was shown to be common in freshwater and marine algae (Khozin-Goldberg and Cohen, 2006;Van Mooy et al, 2009;Martin et al, 2011;Iwai et al, 2015;Cañavate et al, 2017b). Recent studies comparing lipid class and P-uptake profiles of eight algae at low P i showed replacement of phospholipid by BL with concomitant high P uptake in the green alga Tetraselmis suesica and the stramenopiles P. tricornutum, N. gaditana, and P. atomus (Cañavate et al, 2017a(Cañavate et al, , 2017b.…”
mentioning
confidence: 97%
See 3 more Smart Citations